Analisis Profil Wisatawan Mancanegara Yang Keluar Melalui Pintu Soekarno Hatta Dan Ngurah Rai - Juwita Hapsari, Veronika; Nuryakin, Chaikal (Jurnal Kepariwisataan Indonesia: Jurnal Penelitian dan Pengembangan Kepariwisataan Indonesia, 2019)
Indonesia has enormous tourism potential. This potential is spread throughout almost all regions of Indonesia. However, until now Indonesian tourism is only synonymous with Bali. Development of other destinations besides Bali (non-Bali destinations) has begun to take place in almost all parts of Indonesia due to the economic potential of tourism which can drive the region’s economy. Although not as many as Bali, foreign tourists have visited non-Bali destinations. This proves that non-Bali destinations also have the potential to be developed due to tourism demand from tourists. This research aims to profile foreign tourists for non-Bali destinations as one of the steps in developing tourism marketing according to the National Tourism Development Master Plan 2010-2025. In conclusion, tourists who visit non-Bali destinations are predominantly male and repeater